KEBEBASAN BERPENDAPAT DAN BEREKSPRESI DI ERA DIKITAL : PERSPEKTIF HAM - Suherman, Asep; Tasimia, Ayu Nurhaliza (Jurnal Hukum Positum, 2025)
This research discusses the application of human rights principles in the context of armed conflict, with a case study of the long-standing Israeli-Palestinian conflict. Human rights are fundamental rights that should be upheld and protected, even in conflict situations. However, reality shows that there are many human rights violations, especially in the Palestinian territories, which have an impact on the rights to life, freedom and personal safety of civilians. International law, through the Geneva Conventions and Additional Protocols, has established protection for civilian populations and regulates the obligations of conflicting parties to distinguish between combatants and non-combatants, and avoid excessive attacks. However, the implementation of this rule experiences various obstacles which result in human rights violations continuing to occur. This research uses a normative juridical approach with a literature study method, examining relevant international legal rules and related reports. The analysis focuses on the gap between legal norms and practice in the field, which is influenced by political, military and ideological factors of the conflicting parties. Based on research findings, there is an urgent need to find effective solutions to protect human rights in these conflict areas. It is hoped that this research can provide a comprehensive view of the importance of implementing human rights in armed conflict and offer recommendations for more effective human rights protection efforts in the future.